Black-Box Small-Signal Structure for Single-Phase and Three-Phase Electric Vehicle Battery Chargers - Antreas Naziris; Airan Frances; Rafael Asensi; Javier Uceda (IEEE Access, 2020)
At present, it is safe to say that the future belongs to sustainable technologies. Electric vehicles are one of the most representative sustainable solutions for mobility. Some of the many advantages they offer are a clean operation, a profit gain from a possible power return to the grid in vehicle to grid applications, grid power support, etc. As it is expected, an increase in the production of electric cars, and other battery-based systems, lead to an increment in battery chargers. Therefore, energy distributors must deal with many different schemes in the grid and with the amount of energy demanded from a fleet of cars and other electric vehicles. This paper deals with the modeling of AC/DC battery chargers by identifying the transfer functions in any operating condition without knowing the specific details inside those chargers. This approach is called black-box modeling and the strategy is based on the information provided by the input and output variables of the charger. The research illustrates the flexibility of the model to work with single-phase and three-phase AC/DC chargers which are linked to on-board and off-board charging stations. An extensive set of tests is shown, verifying the accuracy of the proposed models in a wide variety of operating conditions.